1992
DOI: 10.1111/j.1365-2265.1992.tb01487.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive inhibin levels during ovarian stimulation may predict granulosa cell maturity

Abstract: These data suggest that in cycles where there are multiple small follicles, E2 secretion is maintained whereas immunoreactive inhibin secretion is substantially lower. Thus, in view of the disparity between E2 and immunoreactive inhibin secretion evident in the MFD group, measurement of immunoreactive serum inhibin concentration may be a better indicator of granulosa cell maturity. Immunoreactive inhibin secretion may occur only from healthy mature follicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Increase of inhibin serum levels is apparently the earlier pharmacodynamic marker that the dose given will be effective, and careful inspection of the data indicates that, if after 1 week of treatment, inhibin serum levels are Ͼ5 U/mL, a significant follicular development reasonably can be expected. Besides being an early index of follicular development, inhibin has been shown to be an index of follicular maturation (22) and a prediction of follicle quality (11). Together, this suggests the need for further investigations of the use of inhibin as a useful clinical index for monitoring FSH treatment.…”
Section: Smentioning
confidence: 99%
“…Increase of inhibin serum levels is apparently the earlier pharmacodynamic marker that the dose given will be effective, and careful inspection of the data indicates that, if after 1 week of treatment, inhibin serum levels are Ͼ5 U/mL, a significant follicular development reasonably can be expected. Besides being an early index of follicular development, inhibin has been shown to be an index of follicular maturation (22) and a prediction of follicle quality (11). Together, this suggests the need for further investigations of the use of inhibin as a useful clinical index for monitoring FSH treatment.…”
Section: Smentioning
confidence: 99%
“…It was reported that human ovarian cystic fluids produced a marked inhibition of FSH-binding activity in the absence of an effect on FSH or LH secretion [38]. Polycystic ovarian syndrome (PCOS) is the most common pathological cystic ovarian disease in human and is associated with a deficit in the paracrine control of folliculogenesis [4]. Autocrine/paracrine factors, especially those which are FSH-dependent, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…They are developmentally and physiologically important growth factors with structural homology to a large group of proteins including the transforming growth factor-β (TGF-β) [51], and have been reported to play a role in cystic ovarian diseases [4,5,19]. Similar to other members of the TGF-β family, inhibins interact with cell surface receptors [29].…”
mentioning
confidence: 99%
“…However, a high degree of assay specificity does not seem to be required for all clinical applications of inhibin measures, as previously suggested (14). For example, ␣-inhibin levels may be used as a valuable index of granulosa cell (GC) activity or maturity (15,16), as the majority of serum immunoreactive inhibin is thought to arise from the GC in nonpregnant women.…”
Section: Nhibins Are Dimeric Glycoproteins Consisting Of Anmentioning
confidence: 91%